Work and motivation - Vroom, Victor Harold (New York Wiley, 1964)
Why do people choose the careers they do? What factors cause peopleto be satisfied with their work? No single work did more to makeconcepts like motive, goal incentive, and attitude part of theworkplace vocabulary.
Bibliography: p. 289-315.
Keywords: Psychology, Industrial